Biorhythmologic mechanisms of desadaptative disorders in a man in Аntarctic region - Ye. V. Moiseyenko (Ukrainian Antarctic Journal, 2008)
In work the results of medical-biological researches of biorhythmologic mechanisms of disorders desadaptation development of the human organism’s functional systems among participants of the long-term Antarctic expedition at the station «Academician Vernadskiy» are presented. It is shown that the long-term stay of a man in Antarctic Region is accompanied seasonal disorders of correlations of rhythms of EEG, rebuildings of day's organization of blood circulation function and temperature of body, what can be accompanied by increasing of functional tension and development of desadaptative disorders what can be driven by pathogenic links of neurohumoural mechanisms.